Influence of Humic Acid on Availability of Zn, Cu, Mn, Fe in Soils - Turkmen, Cafer; Sungur, Ali (Asian Journal of Chemistry, 2014)
The objective of this study was to investigate the influence of an organic substance, humic acid, on availability of extractable Zn, Cu, Mn and Fe in soils. Humic acid was applied in four different doses (0, 3, 6 and 12 L/da) and all treatments were incubated. During the incubation, soil samples were taken at four different times (I, II, IV and VIII weeks). In these soil samples Cu, Fe, Mn and Zn ions were extracted through diethylene triamine pentaacetic acid method and flame atomic absorption spectrometer was used for elemental analyses. Statistical analyses were performed by using MINITAB-16 statistical software program. Results revealed significant differences in Fe, Mn and Zn concentrations of dose-time interaction at p < 0.01 level and in Cu concentrations at p < 0.05 level. The differences in pH values of dose-time interaction were also found to be significant at p < 0.01 level. With regard to sampling times, the differences in electrical conductivity values were found to be significant at p < 0.01 level.